Synthesis and crystal structure of 5,10-dihydroxy-9-methoxy-2,2-dimethyl-12-(2-methylbut-3-en-2-yl)-2H,6H-pyrano[3,2-b]xanthen-6-one - Amporn Saekee; Chutima Kuhakarn; Khetpakorn Chakarawet; Sakchai Hongthong (Acta Crystallographica Section E: Crystallographic Communications)
5,10-Dihydroxy-9-methoxy-2,2-dimethyl-12-(2-methylbut-3-en-2-yl)-2H,6H-pyrano[3,2-b]xanthen-6-one, C24H24O6 (2), is a prenylated xanthone that was synthesized from 5,9,10-trihydroxy-2,2-dimethyl-12-(2-methylbut-3-en-2-yl)-2H,6H-pyrano[3,2-b]xanthen-6-one or macluraxanthone (1), a known compound isolated from Garcinia schomburgkiana Pierre. The present study describes the synthesis of compound 2 by methylation reaction of 1, and its crystallographic characterization. Compound 2 features a planar xanthone core and a bent pyrano ring adopting a half-boat conformation. An intermolecular O—H...O hydrogen bond between the hydroxyl hydrogen donor and the ketone acceptor organizes the molecules into a one-dimensional network along the b-axis direction. Perpendicular to this network, π–π stacking interactions form the three-dimensional supramolecular architecture. These two key intermolecular interactions are distinctly revealed in the Hirshfeld surface analysis.